Pengaruh Pelatihan Efikasi Diri, Kepemimpinan Transformasional Terhadap Stres Kerja Anggota Satuan Brimob Polda Sumut - Halim Perdana Kusuma; M. Rajab Lubis; Suryani Hardjo (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2019)
This study aims to see the effect of self efficacy and transformational leadership on work stress of members of Brimob Polda Unit in Medan. The study was conducted from November 2016 until March 2017. Using the quantitative method of experimentation, using a one group pretest-posttest design. Using purposive sampling method as many as 20 people. Data collection methods in this study using a scale, which consists of work stress scale, self efficacy and leadership scale, where the reliability of the scale work stress for 0.916, reliability self-efficacy scale of 0.963 and the leadership scale of 0.948. Where the three scales are very reliable and worthy used as a measuring tool in this study. The results of self efficacy training showed the significance (p) value of 0.0000.05, which means that there is an effect of self efficacy training on job stress reduction of Sat Brimob members, while the partial research result between leadership variables and work stress has no significant influence. This is seen from the results p of 0.3270.05 and R squere of 0.053 where the leadership contribution is only 5.3% of work stress. While simultaneous research results show the value of self efficacy and leadership significance to work stress of 0.0720.05, which means that there is no significant influence between self efficacy  and leadership to work stress, with a contribution of only 26.6% determination.